2022
DOI: 10.34133/research.0005
|View full text |Cite
|
Sign up to set email alerts
|

Sky Blue and Yellow Cluster Light-Emitting Diodes Based on Asymmetric Cu 4 I 4 Nanocubes

Abstract: Controllably optimizing excited-state characteristics is crucial for luminescent nanoclusters but remains a formidable challenge. Herein, we report an effective “ligand-induced asymmetrization” strategy for constructing thermally activated delayed fluorescence-featured cubic Cu 4 I 4 nanoclusters with asymmetric configurations, named [tBCzDBFDP] 2 Cu 4 I 4 and [PTZDBFDP] 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Phenothiazine (PTZ) with stronger electron donating effect made emission of 25 shifted to orange, whose devices also achieved a favourable EQE reaching 8.6 %. [41] Acridine groups with appropriate electron-donating effect and orthogonal configurations were used to form two mono-substituted DBFDP ligands and corresponding Cu 4 I 4 cubes 26 and 27 with bluish-green TADF. [42] Accelerated singlet radiation and reduced triplet quenching gave rise to their PLQYs reaching 73 % and 81 % for 26 and 27, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenothiazine (PTZ) with stronger electron donating effect made emission of 25 shifted to orange, whose devices also achieved a favourable EQE reaching 8.6 %. [41] Acridine groups with appropriate electron-donating effect and orthogonal configurations were used to form two mono-substituted DBFDP ligands and corresponding Cu 4 I 4 cubes 26 and 27 with bluish-green TADF. [42] Accelerated singlet radiation and reduced triplet quenching gave rise to their PLQYs reaching 73 % and 81 % for 26 and 27, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Cationic Ag 6 Cu-based heteronuclear clusters (41) were stablized with CH(PPh 2 ) 3 and ethynyl ligands, whose PH was attributed to 3 [d!s/p] and 3 LLCT. [50] Based on electronic effects of substituents, the emission color and carrier transportation can be modified to support the maximum EQE reaching 13.9 %.…”
Section: Ag N M M and Au N M M Hybrid Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, on the basis of ligand engineering, we developed a series of bluish green EL Cu 4 I 4 cubic clusters with the state-of-the-art η EQE beyond 20% 39 42 . Nonetheless, despite a single-molecular white-emitting Cu 4 I 4 cluster also demonstrated 43 , there are no white cluster light-emitting devices (CLED) reported until present, since the maximum η EQE of yellow emissive Cu 4 I 4 cubes was still less than 10% 44 . The previous works showed that donor modification can enhance LC components, reduce bandgaps and increase molecular polarity.…”
Section: Introductionmentioning
confidence: 94%
“…26,27 In addition, a substantial number of copper(I)halide clusters are insoluble in conventional solvents and exhibit instability during sublimation, which makes them unsuitable for fabricating cluster light-emitting diodes (CLEDs) via solution-based processes and vacuum deposition. Despite some progress, 10,[28][29][30][31][32][33][34][35] the rational design of copper(I)halide clusters for highly efficient CLEDs and the comprehension of structure-property relationships continue to pose challenges.…”
Section: Introductionmentioning
confidence: 99%